Administrative Dispute against Procedures - Božidar Horvat (Zbornik Radova Pravnog Fakulteta u Splitu, 2014)
Novelties in administrative dispute are pointed out in this paper, that is, an evaluation of the legality of procedures undertaken by public bodies in the administrative law domain which have infringed upon the rights, duties or legal interests of the party who has no recourse to regular legal remedy.